SEJARAH DAN TRANSFORMASI PEMIKIRAN WAHABI: Pengaruh dan Relevansinya dalam Dunia Islam Kontemporer - Kerwanto, Kerwanto; Furqan Alfaruqiy, Muhammd (Jurnal Studi Islam dan Sosial, 2025)
The Wahhabi or Salafi movement is an important phenomenon in contemporary Islamic history, rooted in the preaching of Sheikh Muhammad bin ‘Abd al-Wahhāb in Najd during the 18th century CE. This movement emphasizes the purification of monotheism and the rejection of practices considered deviant from pure Islamic teachings. This study uses a qualitative approach based on literature review to analyze the historical, theological, and sociopolitical dynamics of the Wahabi movement. The findings show that the success of the Wahabi movement lies not only in its ideology but also in its political collaboration with the al-Sa‘ūd dynasty. Despite its wide influence, this movement has also raised controversy due to its rigid and exclusive approach. This article evaluates the relevance of the Wahabi movement in the context of globalization and the future of Islamic civilization.